Co-producing smart cities: A Quadruple Helix approach to assessment. (October 2021) - Paskaleva, Krassimira; Evans, James; Watson, Kelly
Cities are increasingly expected to bring urban stakeholders together to deploy smart solutions that address urban challenges and deliver long-term positive impacts. Yet, existing theory and practice struggle to explain how such impacts can be achieved, measured or evidenced. This paper makes two major contributions. Firstly, the paper shows how the Quadruple Helix (QH) innovation approach can be used as the basis for co-producing smart city projects in order to better capture their impacts. In doing so we present a synthesis of current smart city and QH literatures to argue that assessment criteria and indicators must be co-produced with the full set of smart city stakeholders to ensure relevance to context and needs. Secondly, we present an example of a co-produced monitoring and assessment framework and methodology, developed to capture and measure the impacts of smart and sustainable city solutions with the stakeholder teams involved in the European Union Triangulum smart city programme. The paper draws on experiences working with 27 smart city demonstration projects involving public, private and third-sector organisations and communities across Manchester (United Kingdom), Eindhoven (The Netherlands) and Stavanger (Norway). We show how involving QH stakeholders in co-producing impact assessment improves the ability of projects to deliver and measure impacts that matter to cities and citizens. We conclude with a series of lessons and recommendations intended to be of use to the range of organisations and communities currently involved in smart city initiatives across Europe and the world.